Social and cultural determinants of antibiotics prescriptions: analysis from a public community health centre in North India - Mukherjee, Arunima; Surial, Rashmi; Sahay, Sundeep; Thakral, Yogita; Gondara, Amandeep (Frontiers in Pharmacology, 2024)
It is well established by research that large-scale and indiscriminate prescriptions and use of antibiotics drives antimicrobial resistance (AMR) endangering the health and well-being of people. In the context of low-and middle-income countries (LMICs), overuse of antibiotics has underlying reasons, which may not be based on a medical rationality, but involving an alternative rationally that is shaped by social, cultural and institutional factors. This paper seeks to understand some of these issues to try and answer the question of what means prudent prescribing of antibiotics. This analysis is based on an empirical investigation of prescription slips that patients carry to buy drugs from the pharmacy following an outpatient department (OPD) encounter with the clinician. The analysis yields some interesting findings, such as the widespread use of broad-spectrum antibiotics, and high % of prescriptions from dental OPD, which may be more of a precautionary measure. We also highlight the need for future research insights in combining socio-cultural approached with medical rationalities, to further explore questions our analysis highlights.